The Effect of Formal Performance Evaluation and Intrinsic Religiosity on Trust - Lina; Mahfud Sholihin; Slamet Sugiri; Wuri Handayani (Cogent Business & Management, 2022)
The current COVID-19 pandemic is a worldwide challenge, so organizationsneed to create innovative management to drive effective performance. Effective performance can be achieved, among others, by creating interpersonal trust between employees and supervisors. Therefore, examining the antecedents of this interpersonal trust is an important study. The purpose of this study is to examine the effect of formal performance evaluation system and intrinsic religiosity on a person's trust toward their superiors. Data were obtained using an online questionnaire survey method. A total of 222 full-time faculty members of economics and business from 24 Christian higher education institutions across 14 provinces in Indonesia participated in this study. The data were analyzed using hierarchical regression analysis. This study provides evidence on the positive effect of formal performance evaluation systems on trust based on social exchange theory. This study also reveals that intrinsic religiosity positively influences subordinates' trust in their superiors. This study is, to the best of our knowledge, the first to introduce supernatural monitoring hypothesis as a theoretical base to examine the effect of intrinsic religiosity on trust. Further, this study provides evidence that supernatural monitoring hypothesis is the complementing theory of social exchange theory in building trust.
Keywords: 650; social exchange theory; Formality of performance evaluation; Indonesian Christian higher education; interpersonal trust; intrinsic religiosity; supernatural monitoring hypothesis